Written on the dark - Kay, Guy Gavriel (Ace, 2025)
"Both sweeping and intimate, a majestic novel of love and war that brilliantly evokes the drama and turbulence of medieval France. Thierry Villar is a well-known-even notorious- tavern poet, familiar with the rogues and shadows of that world, but not at all with courts and power. He is an unlikely person, despite his quickness, to be caught up in the deadly contests of ambitious royals, assassins, and invading armies. But he is indeed drawn into all these things on a savagely cold night in his beloved city of Orane. And so Thierry must use all the intelligence and charm he can muster as political struggles merge with a decades-long war to bring his country to the brink of destruction. As he does, he meets his poetic equal in an aristocratic woman and is drawn to more than one unsettling person with a connection to the world beyond this one. He also crosses paths with an extraordinary young woman driven by voices within to try to heal the ailing king-and help his forces in war. A wide and varied set of people from all walks of life take their places in the rich tapestry of this story. A new masterwork from the internationally bestselling author of All the Seas of the World, A Brightness Long Ago, and Tigana, Written on the Dark is an elegant tour de force about power and ambition playing out amid the intense human need for art and beauty, and memories to be left behind"--